Prognostic Importance of Vitamins A, E and Retinol-binding Protein 4 in Renal Cell Carcinoma Patients - Sobotka, Roman; Čapoun, Otakar; Kalousová, Marta; Hanuš, Tomáš; Zima, Tomáš; Koštířová, Milada; Soukup, Viktor (Anticancer research, 2017)
AIM: To assess the prognostic importance of serum levels of retinol, retinol-binding protein 4 (RBP4) and vitamin E at the time of diagnosis in patients with renal cell carcinoma (RCC). PATIENTS AND METHODS: In this prospective study, in a cohort of 102 renal cell carcinoma patients, relationships between serum levels of the aforementioned markers and recurrence-free survival (RFS), overall survival (OS), as well as cancer-specific survival (CSS), were evaluated. The vitamin A and vitamin E levels were determined by high-performance liquid chromatography (HPLC), while the RBP4 level by enzyme-linked immunosorbent assay (ELISA). RESULTS: The median follow-up period was 39 months. Renal cell carcinoma recurred in 9 patients; 23 patients died with 12 of them from RCC. The preoperative vitamin E level was associated to RFS (p=0.02). We found a significant relationship between OS and the level of RBP4 (p=0.002), retinol (p=0.037) and vitamin E (p=0.007). The CSS period was significantly associated with the level of RBP4 (p=0.0001) and retinol (p=0.0003). Patients with an RBP4 level less than 21.0 mg/l at the time of diagnosis had a 13.5-times higher risk of death due to RCC progression; this risk was up to 7.7-times higher with vitamin A levels under 0.52 mg/l. CONCLUSION: Low levels of vitamin A, E and RBP4 at the time of RCC diagnosis are associated with a poorer prognosis after surgery.
Keywords: nádory ledvin; počítačová rentgenová tomografie; plazmatické proteiny vázající retinol; Retinol-Binding Proteins, Plasma; Humans; lidé středního věku; Vitamins; vitaminy; analýza přežití; Vitamin E; předoperační období; Female; Aged; mladý dospělý; dospělí; Vitamin A; Preoperative Period; senioři; lidé; Survival Analysis; Adult; vitamin A; ženské pohlaví; Male; Middle Aged; Tomography, X-Ray Computed; prognóza; Aged, 80 and over; karcinom z renálních buněk; Young Adult; senioři nad 80 let; Carcinoma, Renal Cell; Nephrectomy; mužské pohlaví; nefrektomie; vitamin E; Kidney Neoplasms; Prognosis